Cover Image, Volume 42, Issue 4. Issue 4 (19th April 2022) - Zhang, Xiao; Xu, Yunhua; Ma, Lifang; Yu, Keke; Niu, Yongjie; Xu, Xin; Shi, Yi; Guo, Susu; Xue, Xiangfei; Wang, Yikun; Qiu, Shiyu; Cui, Jiangtao; et al.
Abstract : The cover image is based on the Original Article Essential roles of exosome and circRNA_101093 on ferroptosis desensitization in lung adenocarcinoma by Jiayi Wang et al., https://doi.org/10.1002/cac2.12275 .